2016
DOI: 10.1007/s10499-016-0091-0
|View full text |Cite|
|
Sign up to set email alerts
|

Enhancement of quality of rainbow trout (Oncorhynchus mykiss) flesh incorporating barley on diet without negative effect on rearing parameters

Abstract: Barley concentrations ranging from 0% to 32% (0B, 40B, 80B, 160B and 319B) were incorporated into rainbow trout, Oncorhynchus mykiss (Walbaum) diets. The experiment started with an initial average fish weight of 127.72 ± 5.65 g and finished when they reached commercial weight (final weight between 312-330 g) after 84 days. The inclusion of barley in the diets did not show a significant effect on growth and biometric parameters, fat and carbohydrate digestibilities, however, protein digestibility decreased sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…aw plays an important role on spoilage of fish (Ježek and Buchtová 2014). This is in agreement to the observed with the inclusion of other CHO sources, such as barley (Pinedo et al 2016). The reduction on aw values would help to reduce lipid oxidation and microbial growth, with advantages in shelflife.…”
Section: : Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…aw plays an important role on spoilage of fish (Ježek and Buchtová 2014). This is in agreement to the observed with the inclusion of other CHO sources, such as barley (Pinedo et al 2016). The reduction on aw values would help to reduce lipid oxidation and microbial growth, with advantages in shelflife.…”
Section: : Discussionsupporting
confidence: 85%
“…Carnivorous fish species, including salmonids, the incorporation of digestible carbohydrates (CHO) should not exceed 20% of the diet. Cereals (wheat, barley, oat, corn) have been traditionally the most utilized CHO sources in commercial salmonid diets (Sealey et al 2008, Gaylord et al 2009, Pinedo-Gil et al 2016. However, those ingredients generally contain high fibre and starch content and these, together with the presence of some antinutritional components, produce limitations to the inclusion of plant ingredients on carnivorous fish diets (Oliva-Teles et al 2015).…”
Section: : Introductionmentioning
confidence: 99%
“…Cortisol increases in fin may be explained by the lipophilic nature of cortisol, which can diffuse through cell membranes into several tissues such as fins, mucus or muscle (Bertotto et al 2010). The increase in plasma cortisol levels was expected and has been described in several studies after various stress conditions in teleost species (Weendelar-Bonga 1997, Mommsen et al 1999, Pichavant et al 2002, Bertotto et al 2010, Pinedo-Gil et al 2017. The lowest values observed in fish fed with 8B diets may probably be explained by a possible immunomodulatory effect of barley.…”
Section: Accepted Manuscriptmentioning
confidence: 91%
“…The use of β-glucans has been widely studied in aquaculture (Jeney et al 1997, Meena et al 2013, Al-Faragi 2014, Pinedo-Gil et al 2017. β-glucan is one of the most important immunostimulant (Meena et al 2013) and has been widely studied because it plays an important role in immune system (Zeng et al 2016, Miest et al 2016 protecting fish against stress factors (Dawood et al 2015, Zeng et al 2016.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, the use of alternative natural ingredients, with bioactive compounds that can enhance fish quality and oxidative stability, have not been investigated. Previous work confirmed that the inclusion of barley on rainbow trout diets had an enhancing effect on quality parameters, probably associated to the presence of antioxidant compounds (Pinedo-Gil et al 2017A).…”
Section: Introductionmentioning
confidence: 70%